MENINGKATKAN PRODUKTIVITAS DI LINGKUNGAN KERJA INDUSTRI/PRAKERIN - Maria Evy Purwitasari; Lutviani, Metya; Muhammad Ferdinansyah; Tri Andriani; May Vitha Rahmadhani (POLITEKNIK LP3I JAKARTA, 2024)
To support the process of teaching and learning activities in the vocational field, one of the learning processes is carried out at the SMK level. Every student who graduates from vocational school, as well as students from SMK 1 Barunawati, is required to have skills and be ready to work because vocational school graduates are usually not recognized by the business/industry world. Therefore, a Dual System Education (PSG) program was held, namely by implementing Industrial Work Practices (PRAKERIN) so that every vocational school graduate student has experience in the business world before entering the business world for real after graduating from school. In accordance with the results of observations and research from the Directorate of Vocational Secondary Education, the pattern of implementation at Vocational Schools has not clearly been able to produce graduates as expected. This can be seen from the learning conditions which are not yet conducive to producing professional workers, because a person's professional skills are not solely measured by mastery of knowledge elements and work techniques, but must be complemented by mastery of good work skills. There are two parties, namely educational institutions and employment opportunities (industry/companies or certain agencies) which jointly organize a vocational skills program. Thus both parties should be involved and responsible.